2011
DOI: 10.1038/pcan.2011.13
|View full text |Cite
|
Sign up to set email alerts
|

The effects of combination therapy with dutasteride plus tamsulosin on clinical outcomes in men with symptomatic BPH: 4-year post hoc analysis of European men in the CombAT study

Abstract: CombAT (Combination of Avodart and Tamsulosin) was a randomised, double-blind study in men (n ¼ 4844) aged X50 years with a clinical diagnosis of BPH. Patients were randomised to daily tamsulosin 0.4 mg, dutasteride 0.5 mg or both for 4 years. The primary endpoint was time to acute urinary retention (AUR) or BPH-related surgery. Secondary endpoints included BPH clinical progression, symptoms and maximum urinary flow rate. A post hoc analysis of data from the European subgroup was conducted. A total of 2925 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…One of the LUTS symptoms pathophysiology in BPH patients is increased in smooth muscle tone of the prostate. Selective α1adrenergic receptor antagonist is chosen as a therapy for BPH because it is effective and safe for long-term use [7][8][9][10]. These drugs act on the dynamic component of Bladder Outlet Obstruction (BOO), that reduce smooth muscle tone of the prostate and bladder neck [11].…”
Section: Discussionmentioning
confidence: 99%
“…One of the LUTS symptoms pathophysiology in BPH patients is increased in smooth muscle tone of the prostate. Selective α1adrenergic receptor antagonist is chosen as a therapy for BPH because it is effective and safe for long-term use [7][8][9][10]. These drugs act on the dynamic component of Bladder Outlet Obstruction (BOO), that reduce smooth muscle tone of the prostate and bladder neck [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, LUTS are divided into voiding symptoms and storage symptoms. α-Blockers and 5-androgen receptor inhibitors are an effective medication for men with LUTS [10,11]. However, these medications are not sufficient for managing all patients with LUTS, because LUTS originate not only from pathologic benign prostatic hyperplasia also as a result of a detrusor muscle condition [12].…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapy was shown to lead to greater reductions in storage subscores than dutasteride monotherapy and tamsulosin monotherapy from months 3 and 12, respectively. Recently a 4‐year post hoc analysis of the CombAT data showed that combination therapy also provided significantly greater symptom improvement than either monotherapy at 4 years 19 …”
Section: Discussionmentioning
confidence: 99%
“…Recently a 4-year post hoc analysis of the CombAT data showed that combination therapy also provided significantly greater symptom improvement than either monotherapy at 4 years. 19 Jeong et al examined the effect of discontinuing 5ARIs on prostate volume and symptoms in BPH patients. 20 They divided the patients into two groups giving combination therapy with either finasteride 5 mg or dutasteride 0.5 mg.…”
Section: Discussionmentioning
confidence: 99%